Effect of Aqueous Extract of Tridax procumbens Linn on Plasma Electrolytes of Salt-Loaded Rats - Jude, Ikewuchi C.; Catherine, Ikewuchi C.; Frank, Onwuka C.; Frank, Onwuka C. (Pakistan Journal of Nutrition, 2010)
The effect of aqueous extract of Tridax procumbens Linn on the weight, packed cell volume and plasma electrolyte profiles of salt-loaded rats were investigated. The test and test-control groups received a diet consisting 8% salt and 92% commercial feed, while the control group received a diet consisting 100% of the commercial feed. The test group also received daily by intra-gastric gavages, 50 mg/100 g body weight of the extract, while the test-control and control groups received appropriate volumes of water by the same route. The mean daily weight gain and Packed Cell Volume (PCV) of the test rats were significantly higher (p<0.05) than those of the test-control and control. The treated animals had significantly lower (p<0.05) plasma sodium and chloride levels, compared to the test-control. There was no difference in the plasma calcium and potassium levels of the test and test-control animals. This result suggests that the antihypertensive action of T. procumbens may be mediated via reduction of weight and alteration of plasma sodium and potassium levels and in addition suggest its use in the management of obesity and diabetes mellitus.